Penerapan Metode Simple Additive Weighting (SAW) pada Sistem Informasi Pemilihan Asisten Praktikum - Gustalika, Muhamad Azrino; Rakhmadani, Diovianto Putra; Segara, Alon Jala Tirta (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Each campus has technology that is used to communicate and exchange information using technology in the form of a website. The use of the website itself has penetrated into the world of education, one of which is the laboratory on campus. Laboratory on campusÂ cannotÂ be separated from the existence of a practicum assistant. Every semester the faculty ofÂ informaticsÂ opens registration for practicum assistants, but there are obstacles that candidates who register still use the manual method in their selection. So they need the Simple Additive Weighting (SAW) method. This study uses the Simple Additive Learning method which will increase the highest score level of 1.39 with the weight indicator used in the selection of practicum assistants and get an average score of 4.9 out of 5.0 so that it is very effective for admins (laborers) to manage andÂ lecturers, toÂ see recommendations for prospective practicum assistants, the best are web-based